Human Resource Management Practices, Integrity And Task Performance Among Police Officer In Malaysia - Chong, Kok Yeow (2023)
The study intends to examine the relationship between human resource management (HRM) practices, integrity, and task performance among Royal Malaysia Police (RMP) police officers. The study also intends to examine the mediating roles of job embeddedness, organizational commitment, and job satisfaction between human resource management practices, integrity, and task performance.